2022
DOI: 10.3389/fpsyg.2022.867939
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of Homing Pigeon Spatial Navigation: Results From Electrophysiology Studies

Abstract: Over many centuries, the homing pigeon has been selectively bred for returning home from a distant location. As a result of this strong selective pressure, homing pigeons have developed an excellent spatial navigation system. This system passes through the hippocampal formation (HF), which shares many striking similarities to the mammalian hippocampus; there are a host of shared neuropeptides, interconnections, and its role in the storage and manipulation of spatial maps. There are some notable differences as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 105 publications
1
3
0
Order By: Relevance
“…It has also been suggested that Cluster N may be a specialized region for night navigation using both visual and geomagnetic informational cues [ 4 , 5 , 9 ]. We observed ZENK expression in the hippocampal formation in birds exhibiting night migratory restlessness, similar to other avian studies and the hippocampus has been repeatedly shown to be involved in spatial memory and navigation functions [ 28 , 37 , 38 ]. Zapka and colleagues (2009) lesioned Cluster N in migratory songbirds and disrupted magnetic orientation behavior but not sun or star compass behavior.…”
Section: Discussionsupporting
confidence: 90%
“…It has also been suggested that Cluster N may be a specialized region for night navigation using both visual and geomagnetic informational cues [ 4 , 5 , 9 ]. We observed ZENK expression in the hippocampal formation in birds exhibiting night migratory restlessness, similar to other avian studies and the hippocampus has been repeatedly shown to be involved in spatial memory and navigation functions [ 28 , 37 , 38 ]. Zapka and colleagues (2009) lesioned Cluster N in migratory songbirds and disrupted magnetic orientation behavior but not sun or star compass behavior.…”
Section: Discussionsupporting
confidence: 90%
“…It has also been suggested that Cluster N may be a specialized region for night navigation using both visual and geomagnetic informational cues [31,45,46]. We observed ZENK expression in the hippocampal formation in birds exhibiting night migratory restlessness, similar to other avian studies and the hippocampus has been repeatedly shown to be involved in spatial memory and navigation functions [23,24,38]. Zapka and colleagues (2009) lesioned Cluster N in migratory songbirds and disrupted magnetic orientation behavior but not sun or star compass behavior.…”
Section: Discussionsupporting
confidence: 87%
“…However, so far only very few studies target this issue in any non-mammalian species. Some pioneering works in pigeons (Bingman et al, 2003;Hough andBingman, 2004, 2008;Siegel et al, 2005Siegel et al, , 2006Kahn et al, 2008) reported hippocampal cells with similar response properties to those of rats, which were however not so clearly defined as in rats (Bingman and Sharp, 2006;Hough, 2022). The first demonstration of clearly defined place cells in birds, came much more recently (Payne et al, 2021).…”
Section: Do Chicks Have Place Cells?mentioning
confidence: 99%
“…However, until recently, only one study directly investigated the role of chicks' hippocampus in spatial tasks (Tommasi et al, 2003). We have thus performed a series of experiments using neural activity markers (the immediate early gene product c-Fos) to systematically investigate the involvement of chick hippocampus in different spatial tasks (Mayer et al, 2016(Mayer et al, , 2018, 2022. Immediate early genes are expressed in response to neural activation and their products are often used to map neural activation in mammals and in birds (Lanahan and Worley, 1998;Tischmeyer and Grimm, 1999;Smulders and DeVoogd, 2000;Kubik et al, 2007;Golüke et al, 2019;Corrales Parada et al, 2021).…”
Section: Introductionmentioning
confidence: 99%